The Use of Mind-Mapping to Improve Student's Reading Comprehension At SMAN 1 Grati Pasuruan - Ayudyah, Saraswati; Sumarsono, Puji (University of Muhammadiyah Malang, 2014)
An Investigation on Team Teaching Implemented by Local and Foreign Teachers in Teaching English at SMAN 1 Ketapang Sampang